2022
DOI: 10.1002/alz.12818
|View full text |Cite
|
Sign up to set email alerts
|

Association of change in cardiovascular risk factors with incident dementia

Abstract: Introduction:We evaluated whether better cardiovascular health at midlife and improvement of cardiovascular health within midlife were associated with dementia risk. Methods: Two longitudinal population-based studies were used: Atherosclerosis Risk in Communities (ARIC) (n = 11,460/visits at ages 54 and 60), and Age, Gene/Environment Susceptibility (AGES)-Reykjavik (n = 3907/visit at age 51). A cardiovascular health score (range 0-12/0-14, depending on diet availability) including six/seven items was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“… 35 Exposure to cardiovascular risk factors, in particular in midlife and in a cumulative manner, is strongly linked with incident dementia in later life. 36 We and others have shown that the buildup of pathologies at the level of heart and extracranial vessels results in accelerated brain parenchymal loss, cerebral small‐vessel disease, and cognitive impairment. 37 , 38 Although the role of extracranial carotid disease in cognitive impairment has been extensively evaluated, there are limited comprehensive data on the role of intracranial atherosclerosis in brain structural and functional changes.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Exposure to cardiovascular risk factors, in particular in midlife and in a cumulative manner, is strongly linked with incident dementia in later life. 36 We and others have shown that the buildup of pathologies at the level of heart and extracranial vessels results in accelerated brain parenchymal loss, cerebral small‐vessel disease, and cognitive impairment. 37 , 38 Although the role of extracranial carotid disease in cognitive impairment has been extensively evaluated, there are limited comprehensive data on the role of intracranial atherosclerosis in brain structural and functional changes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the observed decreasing risk of CV risk factors or diseases for incident dementia with increasing age might be due to the fact that our studied outcome was all-cause dementia and that the presence of multiple pathologies, rather than vascular dementia on its own, seems to be involved in the development as age increase. Fifth, we should have been taking into account the CV risk level in the risk prediction of dementia with longitudinal data since, the improvement of CV modi able risk was associated with a reduction of dementia risk [48][49][50]. Finally, we did not take into account the impact of level adherence of CV medication.…”
Section: Discussionmentioning
confidence: 99%
“…CVD risk calculators which incorporate multiple risk factors produce a single risk score and are a standard tool to identify an individual's cardiovascular risk over a specified period. There is some evidence that these CVD risk scores may also be associated with cognitive decline [8][9][10][11][12][13][14][15][16], especially in middle-age [8,9,12,15,16]. Evidence of a relationship between CVD risk scores and cognition in later life (aged >70 years) is mixed [10,11,13], and very few studies have looked at the association between CVD risk scores and the incidence of dementia [17][18][19].…”
Section: Introductionmentioning
confidence: 99%